A migração de jovens do campo - Bezerra, Lucas Wanderson Silva (Universidade Federal do Tocantins, 2022)
The present work is a systematization of the experiences and experiences in the field research carried out in the Paulo Freire II settlement in Rios dos Bois - TO, through successive approaches to reality in order to know and understand the migratory flow of young people from rural areas to the environment urban, organization, socioeconomic conditions and societal transformations within the settlement. In view of these conditions, we analyzed the profile and socioeconomic status of the settlers in order to understand the local youth migration movement, and the public policies present in the settlement. The rural migration process, in turn, stands as a response to the difficulties of material existence for families in the countryside; on the other hand, there is an emptying of the rural environment, the increase of poverty in cities and, consequently, generating in life of these people a rejection of these immigrants in the labor market. In the research, we identified the motivations that lead young settlers to migrate to the city and the reasons for the aging of rural dwellers. The results found in the settlement Paulo Freire II, showed to be promising. The interviewees, these residents in the settlement 59.4% are men, only 6.4% are young people aged between 23 and 27 years old.This information gathered on the spot also indicated that few residents who came from the BR-153 encampment participated in the movement, those families who fought for the settlement to be constituted.